2020
DOI: 10.1007/s13177-020-00235-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Crossing Collision Accident Characteristics by Accident Party

Abstract: This paper shows the characteristics of crossing collision accident by accident party. As Fukuoka Prefecture has the third most accidents in Japan, we selected Hakata and Chuo Ward in Fukuoka city as the target of the investigation. We investigated 1,810 crossing collision accidents and 2,662 intersections' environmental factors such as traffic lights and intersection shape. In addition, we classified the accidents into car to car accidents and car to bicycle accidents according to the type of accident parties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…At intersections, bicycle crashes are found to be inversely proportioned to the width of pedestrian pavements (Kim et al, 2012). It was also found that bicycle crashes are more likely to happen at intersections with stop signs compared to no-stop signs intersections (Dong et al, 2021). Moreover, a study found that cyclists who were turning left at an intersection were more exposed to traffic crashes (Yuan and Chen, 2017).…”
Section: Evaluating Bicycle Lanes and Stations Safety Inmentioning
confidence: 99%
“…At intersections, bicycle crashes are found to be inversely proportioned to the width of pedestrian pavements (Kim et al, 2012). It was also found that bicycle crashes are more likely to happen at intersections with stop signs compared to no-stop signs intersections (Dong et al, 2021). Moreover, a study found that cyclists who were turning left at an intersection were more exposed to traffic crashes (Yuan and Chen, 2017).…”
Section: Evaluating Bicycle Lanes and Stations Safety Inmentioning
confidence: 99%